2013
DOI: 10.1002/lary.23929
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenated fixation demonstrates novel and improved ultrastructural features of the human endolymphatic sac

Abstract: The results in the present study indicate an improvement in obtaining human tissue with optimal fixation for ultrastructural analysis and provide several novel morphologic observations. The potential functions of the endolymphatic sac are discussed with reference to former studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…After a 24-h fixation, the fixative was replaced with 0.1 M PBS and a 0.1 M Na-EDTA solution at pH 7.4 for decalcification (Tylstedt et al 1997). To further improve fixation and ultrastructural preservation, one cochlea was fixed in 2 % glutaraldehyde in an oxygenated fluorocarbon blood-substitute vehicle (Møller et al 2013; fixative provided by Klaus Qvortrup, Copenhagen Department of Anatomy). Human specimens were analyzed at inner ear research laboratories in Uppsala and Innsbruck.…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
“…After a 24-h fixation, the fixative was replaced with 0.1 M PBS and a 0.1 M Na-EDTA solution at pH 7.4 for decalcification (Tylstedt et al 1997). To further improve fixation and ultrastructural preservation, one cochlea was fixed in 2 % glutaraldehyde in an oxygenated fluorocarbon blood-substitute vehicle (Møller et al 2013; fixative provided by Klaus Qvortrup, Copenhagen Department of Anatomy). Human specimens were analyzed at inner ear research laboratories in Uppsala and Innsbruck.…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
“…Thus, definitive conclusions should be made with caution. However, a previous study using the same refined surgical approach in obtaining specimens has not found obvious morphological changes in the human ES (5). Secondly, the use of dura tissue for control may not be adequate for ES, which thus represents a limitation to this study.…”
Section: Discussionmentioning
confidence: 87%
“…Although the function of the human endolymphatic sac is still in general poorly understood, a primary function as a fluid and ion transporter in maintenance of the delicate homeostasis of the endo-and perilymph within the inner ear has been assigned. The proposed functions have been substantiated mostly by classical immunohistochemistry (1Y4) and morphological studies (5) in both animals and humans, as well as recent gene arrays in rats (6). These reports suggest that the epithelial lining of the inner ear, including the ES, appear to have functional equivalents with the kidney.…”
mentioning
confidence: 98%
“…Diapedesis and infiltration of leukocytes may occur from the nearby fenestrated capillaries, mediated by antigen presentation in the ES . The conflicting reports on the existence of immune‐competent cells in the ES could be explained by a proposed recycling traffic of cells, which may again relate to a primary, humoral innate immune defense capacity of the ES.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Additionally, the na€ ıve ES may not be equipped with immune competent cells because animal studies report only very few, if any, leukocytes in the lumen under sterile conditions, [10][11][12] and observations in human tissue may prove to be artifacts. 13 Diapedesis and infiltration of leukocytes may occur from the nearby fenestrated capillaries, 13 mediated by antigen presentation in the ES. 8,14 The conflicting reports on the existence of immune-competent cells in the ES could be explained by a proposed recycling traffic of cells, 5,11 which may again relate to a primary, humoral innate immune defense capacity of the ES.…”
Section: Introductionmentioning
confidence: 99%